Program Pencegahan Demam Berdarah Dengue Melalui Lomba Jentik Nyamuk di Kelurahan Tanjung Uma - Rita Juniati,; Muhammad Chandra Ramadhan,; Syahrani Feisha,; Risti Fisla Mirana,; Rismalia Putri,; Rizki Rizki,; Sanisah Sanisah,; Roberta Bella,; Syahrivan Syahrivan,; Ryan Anggiat Simanjuntak, (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Dengue Hemorrhagic Fever (DHF) remains a serious public health problem in Indonesia, especially in densely populated urban areas with poor sanitation. This condition motivated the implementation of a community service program in Tanjung Uma Village, Lubuk Baja, aimed at increasing community awareness and participation in DHF prevention through an innovative approach. The community acted as an active partner in the program to ensure sustainability. The method used was a Mosquito Larvae Competition among Neighborhood Units (RT), conducted through four stages: socialization, community preparation, field assessment, and appreciation. Socialization provided education on DHF transmission and prevention, followed by collective environmental cleaning activities. Field assessments evaluated environmental cleanliness and mosquito larvae presence, while appreciation served as motivation through recognition. The results showed increased public awareness of environmental hygiene and the application of the 3M Plus program. High participation was reflected in household involvement, the formation of independent larvae monitoring teams (jumantik), and creative initiatives such as planting mosquito-repellent plants and recycling waste. Overall, the program successfully promoted behavioral change and strengthened community solidarity.